2000
DOI: 10.1021/la0004045
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of Modified HIV-1 Capsid p24 Protein onto Thermosensitive and Cationic Core−Shell Poly(styrene)−Poly(N-isopropylacrylamide) Particles

Abstract: The adsorption of HIV-1 capsid p24 protein bearing six histidine residues (named RH24) onto well-characterized thermosensitive and cationic poly(styrene)−poly(N-isopropylacrylamide) core−shell particles was investigated as a function of temperature, pH, incubation time, and salinity. The maximum amount of adsorbed RH24 was observed when the temperature was above the lower critical solution temperature (LCST) of the hydrogel, whereas a negligible adsorbed amount occurred below the LCST. Adsorption isotherms wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
67
0
2

Year Published

2003
2003
2009
2009

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(70 citation statements)
references
References 26 publications
(44 reference statements)
1
67
0
2
Order By: Relevance
“…[191] As predicted by numerous studies, at T > VPTT of pNIPAm a higher adsorption was observed which was due to hydrophobic interactions. Similarly Urakami et al studied the phagocytosis of polystyrene-co-polyacrylamide gel particles as a function of hydrophobicity.…”
Section: Biomaterialsmentioning
confidence: 63%
“…[191] As predicted by numerous studies, at T > VPTT of pNIPAm a higher adsorption was observed which was due to hydrophobic interactions. Similarly Urakami et al studied the phagocytosis of polystyrene-co-polyacrylamide gel particles as a function of hydrophobicity.…”
Section: Biomaterialsmentioning
confidence: 63%
“…[40][41][42][43] Thus it is expected as ppNIPAM surface wettability drops above the LCST, the apparent affinity of soluble protein with the surface increases. 44 Also of note, we find that although the ⌫ max values on PET and ppNIPAM are relatively similar for BSA and antiferritin antibody isotherms, those for fibrinogen adsorption vary with respect to surface and temperature. At 37°C, the ⌫ max values for fibrinogen on both PET and ppNIPAM surfaces are about 550 ng/ cm 2 .…”
Section: A Protein Adsorptionmentioning
confidence: 69%
“…[14] Therefore, immobilization research has largely focused on matrix selection and on optimizing immobilization conditions. [15][16][17][18] For example, work has addressed support surface hydrophobicity/hydrophobocity [19,20,21] and 3 enzyme solution pH. [17,22,23] These parameters have large influence on the total amount of enzyme loading and enzyme-catalyst activity.…”
Section: Introductionmentioning
confidence: 99%